Principles and prospects of high-energy magnesium-ion batteries. (1st September 2015) - Foot, Peter
In the last decade or so, lithium batteries have gained important niche positions in the market for electrochemical storage systems. Their energy capacities per unit weight (or volume) are remarkably better than those of traditional batteries – yet they appear to be approaching their practical limit, and alternative cell systems are under active investigation. The potential advantages of replacing lithium by magnesium have long been recognised, but for years it was thought that materials limitations and technical problems would prevent them from being realised. However, a combination of commercial pressures and recent scientific breakthroughs has made it likely that magnesium batteries will soon be available for a wide range of applications; they are expected to be cheaper and safer than those based on lithium, with comparable performance. This article briefly reviews the current situation and looks at the general background, principles and cell components, outlining some of the technical problems and discussing some promising materials for magnesium-ion batteries.